2016
DOI: 10.1021/acs.cgd.6b01110
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-Controlled Synthesis of Hexagonal Boron Nitride Crystals by Chemical Vapor Deposition

Abstract: Synthesis of hexagonal boron nitride (hBN) crystals with a controlled morphology is a major challenge due to various kinetic and thermodynamic factors at the edge. Supplying BN building blocks by heating precursor ammonia borane at a temperature of 90 °C produced triangular crystals, whereas, at higher heating (130 °C), hBN crystals with a hexagonal morphology were observed. The shape of crystals could also be modulated from hexagonal to triangular under a continuous reduced supply of BN building blocks. We at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Furthermore, the content of precursor in feedback is vital for the growth of 2D materials, [ 90–97 ] it can be also employed to tune the growth behaviors of h‐BN crystals. [ 80,82,98 ] This phenomenon is attributed to the modulated ratio of diffusion and availability of active N and B radicals, which makes crystal growth for either favorable triangular shape with N terminated edges or hexagonal shape with alternating N and B terminated edges. [ 80,82,98 ] It has been reported that the shapes of h‐BN single crystals can be tailored from triangular to truncated triangular and further to hexagonal by simple moving away the Cu substrate from the CVD tube inlet.…”
Section: Cvd Growth Of H‐bn Flakes and Filmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the content of precursor in feedback is vital for the growth of 2D materials, [ 90–97 ] it can be also employed to tune the growth behaviors of h‐BN crystals. [ 80,82,98 ] This phenomenon is attributed to the modulated ratio of diffusion and availability of active N and B radicals, which makes crystal growth for either favorable triangular shape with N terminated edges or hexagonal shape with alternating N and B terminated edges. [ 80,82,98 ] It has been reported that the shapes of h‐BN single crystals can be tailored from triangular to truncated triangular and further to hexagonal by simple moving away the Cu substrate from the CVD tube inlet.…”
Section: Cvd Growth Of H‐bn Flakes and Filmsmentioning
confidence: 99%
“…[ 80,82,98 ] This phenomenon is attributed to the modulated ratio of diffusion and availability of active N and B radicals, which makes crystal growth for either favorable triangular shape with N terminated edges or hexagonal shape with alternating N and B terminated edges. [ 80,82,98 ] It has been reported that the shapes of h‐BN single crystals can be tailored from triangular to truncated triangular and further to hexagonal by simple moving away the Cu substrate from the CVD tube inlet. [ 82 ] The shape variation of h‐BN crystals was attributed to different ratios of boron to nitrogen active species concentrations inside the CVD reactor.…”
Section: Cvd Growth Of H‐bn Flakes and Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…hBN can be considered as a structural analogue of graphene, which is composed of alternating boron and nitrogen atoms in a honeycomb lattice rather than the carbon atoms. Graphene with a zero bandgap is a semimetallic as discussed in Section 1, while hBN with a bandgap of ~6 eV is insulating [100][101][102][103][104][105][106][107]. Significant carrier mobility of graphene has been achieved on atomically flat hBN as a dielectric layer for the FET device.…”
Section: Graphene-hexagonal Boron Nitride Heterostructurementioning
confidence: 99%
“…1. [5][6][7][9][10][11][12][13][14][15][16][17][18][19][20][21][22] It is in order to grow h-BN with a higher growth rate and simultaneously guarantee the lateral size.…”
Section: Introductionmentioning
confidence: 99%